2012
DOI: 10.1111/j.1399-3046.2012.01786.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful haploidentical PBSCT with subsequent T‐cell addbacks in a boy with HyperIgM syndrome presenting as severe congenital neutropenia

Abstract: HIGM syndrome is a group of primary immunodeficiency disorders characterized by recurrent bacterial and opportunistic infections; it is also associated with normal to elevated serum IgM levels and a concomitant deficiency of IgG, IgA, and IgE. In this report, we give account of a boy with X-linked HIGM and a novel Y172C mutation within his CD40LG gene. He presented with severe neutropenia as the dominating symptom. His bone marrow showed maturation arrest at the promyelocyte/myelocyte stage, typical of congeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 11 publications
3
19
0
1
Order By: Relevance
“…Conservative management consists of immunoglobulin replacement therapy, prophylaxis against PJP, granulocyte‐colony stimulating factor (GCSF) for severely neutropenic patients, rCD40L therapy, and measures to decrease the risk of cryptosporidium infections, such as avoiding swimming in ponds and lakes and drinking boiled water . However, the only curative therapy is allogeneic hematopoietic stem cell transplantation (HSCT), as suggested by limited published data . Also, advances in diagnosis, donor selection, preparative regimens, and supportive care have led to improved outcomes following transplantation for primary immunodeficiencies .…”
Section: Introductionmentioning
confidence: 99%
“…Conservative management consists of immunoglobulin replacement therapy, prophylaxis against PJP, granulocyte‐colony stimulating factor (GCSF) for severely neutropenic patients, rCD40L therapy, and measures to decrease the risk of cryptosporidium infections, such as avoiding swimming in ponds and lakes and drinking boiled water . However, the only curative therapy is allogeneic hematopoietic stem cell transplantation (HSCT), as suggested by limited published data . Also, advances in diagnosis, donor selection, preparative regimens, and supportive care have led to improved outcomes following transplantation for primary immunodeficiencies .…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Since Kolb et al first reported sustained remission after DLI in patients with CML relapse after allogeneic BMT in 1990, 16 unmanipulated DLI has become the mainstay allogeneic cellular therapy. However, owing to high risk of GVHD, 17,18 broad use of this monotherapy had been limited until 1996 when an Israeli group described a new approach using lymphocytes treated in vivo or in vitro with recombinant IL-2, by which better therapeutic response was achieved even in those who were previously resistant to unmanipulated DLI. 19 The aim of using DLI in hematological malignancies is to enhance the responsiveness and, at the same time, to lessen the toxicity.…”
Section: Modified Therapeutic DLImentioning
confidence: 99%
“…The availability of donor blood/bone marrow for posttransplant immunological manipulations played a crucial role in graft rejection prophylaxis and establishing sustained and stable donor chimerism. In the setting of non-malignant disease, GVHD confers no advantage and therefore donor lymphocyte infusion (DLI) with the associated high risk of GVHD, has been only used exceptionally [14,15]. Nevertheless, the presented case demonstrates efficacy of DLI in the induction of donor chimerism.…”
Section: Discussionmentioning
confidence: 88%